The soul of the silver dog - Hall, Lynn. (New York : Random House, 1994)
Feeling rejected by her own family after her younger sister's death, fourteen-year-old Cory adopts a blind show dog and devotes herself to bringing back some of his championship glory by training him for agility competition.
"Bullseye books."
Originally published: San Diego : Harcourt Brace Jovanovich, c1992.
Keywords: Dogs -- Fiction; Dog shows -- Fiction